PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR DRIBBLE SEPAKBOLA (STUDI PADA SISWA KELAS X SMA NEGERI 1 GEDANGAN) - LUTFI DONNY PRATAMA, M. (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Success or failure of physical education learning is strongly influenced by the level of skill and creativity of physical education teachers. If a physical education teacher is still monotone in using learning model during the learning process, the students tend to be passive and will certainly affect to learning results. Therefore, a physical education teacher must have skills and appropriate creativity to be able to use and develop a variety of existing learning model, especially on learning soccer dribbles. Based on this, the researcher formulating the statement of problem, whether there is influence and how much influence the implementation of cooperative learning model think pair share (TPS) on learning outcomes soccer dribble in Tenth grade SMA Negeri 1 Gedangan. The type of research is a experimental with quantitative approach. The experimental research used because in this study will be given to the treatment of research subjects. In this research, researchers used a randomized study design pretest-posttest control group design. Researchers used population are students of tenth grade SMA Negeri 1 Gedangan, consist of 2 classes totaling 70 students. The samples were students of tenth grade IPS 1 as the experimental group totaled 35 students and IPS 2 as the control group numbered 35 students was taken by cluster random sampling. Judging from result statistical calculations conclude that there is a significant effect of whole practice method using a modified game of foodball dribbling towards learning outcomes as  evidenced  from the  values  ??thitung  7,531  >  ttabel 2, 032 with a significance level of 0,05. While the greatest effect is found to be 37,22%.  Keywords: learning models, cooperative, think pair share (TPS), learning outcomes, soccer dribble.